Geographic disparities in residential proximity to colorectal and cervical cancer care providers. Issue 5 (8th November 2019) - Hung, Peiyin; Deng, Songyuan; Zahnd, Whitney E.; Adams, Swann A.; Olatosi, Bankole; Crouch, Elizabeth L.; Eberth, Jan M.
Abstract : Background: Persistent rural‐urban disparities for colorectal and cervical cancers raise concerns regarding access to treatment providers. To the authors knowledge, little is known regarding rural‐urban differences in residential proximity to cancer specialists. Methods: Using the 2018 Physician Compare data concerning physician practice locations and the 2012 to 2016 American Community Survey, the current study estimated the driving distance from each residential zip code tabulation area (ZCTA) centroid to the nearest cancer provider of the following medical specialties involved in treating patients with colorectal and cervical cancer: medical oncology, radiation oncology, surgical oncology, general surgery, gynecological oncology, and colorectal surgery. Using population‐weighted multivariable logistic regression, the authors analyzed the associations between ZCTA‐level characteristics and driving distances >60 miles to each type of specialist. ZCTA‐level residential rurality was defined using rural‐urban commuting area codes. Results: Nearly 1 in 5 rural Americans lives >60 miles from a medical oncologist. Rural‐urban differences in travel distances to the nearest cancer care provider(s) increased substantially for cancer surgeons; greater than one‐half of rural residents were required to travel 60 miles to reach a gynecological oncologist, compared with 8 miles for their urban counterparts. Individuals residing within ZCTAs with a higher poverty rate, those of American Indian/Alaska Native ethnicity, and/or were located in the South and West regions were more likely than their counterparts to be >60 miles away from any of the aforementioned providers. Conclusions: The substantial travel distances required for rural, low‐income residents to reach a cancer specialist should prompt a policy action to increase access to specialized cancer care for millions of rural residents. Abstract : Travel distances to cancer specialists appear to be greater for individuals residing in rural communities with higher poverty rates and/or with a higher percentage of American Indian/Alaska Native individuals. We must ensure that these accessibility gaps do not compromise cancer treatments and survival for vulnerable populations.